(untitled) (Journal of Engineering, 2019)
Theoretical trends have appeared Which posed the concept of biological structures in contemporary architecture concept, Spread through the emergence of architectural production that reflect and indicate the nature of the construction structures based on the ideas and principles of biological structures in biological science: Despite the emergence of many architectural proposals that tried to explain the concept in the field of architecture, but it is not dealt with in depth and not given a comprehensive definition: So there was need to search for the concept and its beginning in the biological field as a general framework down to the field of architecture for the purpose of reducing the limits of their search framework Through cognitive survey for the appearance of biological structures in production architectural that led to find previous studies to discover the knowledge gap and identify research problem which states( the presence of cognitive deficiencies demonstrates nature of the biological structures in contemporary architecture in general and in the work of architecture caltrava specially) and was determined a goal of research ( Build a conceptual framework illustrates the nature of the biological structures in contemporary architecture in general and in the work of architecture caltrava specially ) and this need requests it theoretical framework has been drawn from asset of architectural studies. Two main vocabulary (simulated biological, biological structures properties,) and application this vocabulary on three projects for Caltrava then subtract search results and to reach final conclusions and recommendations.